Pengaruh Suhu Penyimpanan Terhadap Kualitas Organoleptik Minuman Probiotik Susu Biji Nangka (Artocarpus heterophyllus) - Ridha Nirmalasari; Misbah Norrahmah; Nurul Septina (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2023)
The seeds of the jackfruit (Artocarpus heterophyllus) have not been used more by the community to make various processed food products. Even though jackfruit seeds contain many nutrients, especially potassium. Jackfruit seeds are rich in nutrients, especially carbohydrates, potassium, phosphorus and fat. The jackfruit seed contains 165 kcal of energy and 36.7 kcal of carbohydrates, which is quite high compared to the content of young jackfruit and ripe jackfruit. Seeing the content of jackfruit seeds which are rich in nutrients, these jackfruit seeds can be an alternative as a raw material for processing vegetable milk. Vegetable milk can be used as a basic ingredient for making probiotic drinks to increase the value of the benefits of this vegetable milk. This study used the Lactobacillus casei bacteria which acts as a probiotic bacteria. The study was conducted with different treatments at 20°C, 25°C, 30°C, and 37°C. Each treatment was repeated 4 times and 24 experimental samples were obtained. Based on the results of the study, it was shown that storage temperature had a significant effect on the organoleptic quality of probiotic jackfruit seed milk in terms of color and taste, but had no significant effect on the aroma parameters of probiotic jackfruit seed milk.